Electron-Deficient Zn-N6 Configuration Enabling Polymeric Carbon Nitride for Visible-Light Photocatalytic Overall Water Splitting - Zhao, Daming; Wang, Yiqing; Dong, Chung‑Li; Meng, Fanqi; Huang, Yu‑Cheng; Zhang, Qinghua; Gu, Lin; Liu, Lan; Shen, Shaohua (Nano-Micro Letters, 2022)
Despite of suitable band structures for harvesting solar light and driving water redox reactions, polymeric carbon nitride (PCN) has suffered from poor charge transfer ability and sluggish surface reaction kinetics, which limit its photocatalytic activity for water splitting. Herein, atomically dispersed Zn-coordinated three-dimensional (3D) sponge-like PCN (Zn-PCN) is synthesized through a novel intermediate coordination strategy. Advanced characterizations and theoretical calculations well evidence that Zn single atoms are coordinated and stabilized on PCN in the form of Zn-N6 configuration featured with an electron-deficient state. Such an electronic configuration has been demonstrated contributive to promoted electron excitation, accelerated charge separation and transfer as well as reduced water redox barriers. Further benefited from the abundant surface active sites derived from the 3D porous structure, Zn-PCN realizes visible-light photocatalysis for overall water splitting with H2 and O2 simultaneously evolved at a stoichiometric ratio of 2:1. This work brings new insights into the design of novel single-atom photocatalysts by deepening the understanding of electronic configurations and reactive sites favorable to excellent photocatalysis for water splitting and related solar energy conversion reactions. Highlights: 1 Atomically dispersed Zn-anchored 3D sponge-like polymeric carbon nitride (Zn-PCN) characteristic of a unique Zn-N6 electron-deficient configuration is synthesized via an intermediate coordination strategy. 2 The electron-deficient Zn-N6 configuration contributes to enhanced electron excitation, accelerated charge separation and transfer as well as reduced overpotentials of water redox reactions. 3 The obtained Zn-PCN realizes photocatalytic overall water splitting to stoichiometrically produce H2 and O2 with good durability under visible light.